Edge State Quantum Interference in Twisted Graphitic Interfaces. Issue 14 (13th March 2022) - Oz, Annabelle; Dutta, Debopriya; Nitzan, Abraham; Hod, Oded; Koren, Elad
Abstract: Zigzag edges in graphitic systems exhibit localized electronic states that drastically affect their properties. Here, room‐temperature charge transport experiments across a single graphitic interface are reported, in which the interlayer current is confined to the contact edges. It is shown that the current exhibits pronounced oscillations of up to ≈40 µA with a dominant period of ≈5 Å with respect to lateral displacement that do not directly correspond to typical graphene lattice spacing. The origin of these features is computationally rationalized as quantum mechanical interference of localized edge states showing significant amplitude and interlayer coupling variations as a function of the interface stacking configuration. Such interference effects may therefore dominate the transport properties of low‐dimensional graphitic interfaces. Abstract : Graphitic systems with zigzag edges exhibit strongly confined electronic edge states. Here, room‐temperature charge transport experiments across a laterally confined twisted graphitic interface are reported. It is shown that the current exhibits oscillations with a dominant period of ≈5 Å that do not directly correspond to graphene lattice spacing, but originates from quantum mechanical interference between localized edge states.